Exposure, access and interaction: A global analysis of sponsorship of nursing professional associations. (7th February 2022) - Grundy, Quinn; Millington, Anna; Robinson, Andrea; Held, Fabian; Fabbri, Alice
Abstract: Aim: To analyse the nature and extent of sponsorship of nursing professional associations and their major scientific conferences. Design: Cross‐sectional content analysis. Methods: Data were extracted from the websites and conference documents of 156 national and international professional nursing associations in 2019 to identify sponsors. Sponsorship prospectuses were analysed to estimate the value and describe the nature of sponsorship arrangements. We analysed sponsorship patterns using social network analysis. Results: Most associations (84/156, 54%) did not report any sponsors. Sponsorship was concentrated among specialty nursing associations in high‐income countries. Half of identified sponsors promoted products used in clinical care (50%; 981/1969); the majority represented the medical device industry (69%; 681/981). Top sponsors generally favoured opportunities that promoted interaction with conference attendees. Conclusion: Globally, commercial sponsorship of nursing associations is a common, but not the dominant source of support for these activities. Half of sponsors were commercial entities that manufactured or distributed products used during clinical care, which presents a risk of commercial influence over education and ultimately, clinical practice. Sponsors favoured opportunities to interact directly with nurses, determine educational content, or foster continued interaction.